Dinamika Kompetensi Pedagogik Guru Pendidikan Agama Islam di Era Modern Perspektif UU 14/2005 - Syach Dilla Bi Rizqi Yahya; Putri Nabilla Syafa Ningtyas; Moh Faizin (ALSYS, 2026)
Pedagogical competence is a key indicator of the professionalism of Islamic Religious Education (PAI) teachers amid developments in modern-era education, as regulated in Law Number 14 of 2005 concerning Teachers and Lecturers. This study aims to examine the dynamics of the pedagogical competence of PAI teachers in the modern era and assess its conformity with the competency standards stipulated in the law. This study employed a qualitative approach with a library research design through the examination of relevant legislative documents, books, and scientific journal articles. Data were analyzed using content analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the pedagogical competence of PAI teachers in the modern era includes the ability to understand students’ characteristics, design and implement innovative learning, utilize technology in the learning process, evaluate learning outcomes, and optimally develop students’ potential. Nevertheless, its implementation still faces challenges, particularly in the aspects of learning innovation and the maximum use of technology. The conclusion of this study affirms that strengthening the pedagogical competence of PAI teachers needs to be carried out continuously so that it remains aligned with the demands of teacher professionalism in the modern era. The implications of this study emphasize the importance of continuous training and teacher professional development as strategies to improve the quality of PAI learning and ensure the alignment of pedagogical practice with the applicable teacher competency standards.